RESISTENSI KAYU PLASTIK TERHADAP TIGA JENIS JAMUR PERUSAK KAYU - Ginuk Sumarni; Jasni Jasni (Jurnal Penelitian Hasil Hutan, 1989)
Wood plastic  composite   samples  made,  from  rubber  wood  (Hevea brasilliensis  Muell.  Arg.)  were tested  for durability againts  Shizophyllum commune Fr,  Pycnoporus sanguineus (Fr.) Karst  and  Dacryopinax  spathularia   (Schw.)  Mart,  fungi. The  results  shows  that   rubber  wood  plastic  composite   is not  resistance  againts  the above  three  wood  destroying   fungus.